PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA BARISTA DI STARBUCKS JAKARTA - Diana Sari Ariyani; Nasrullah (LPPM Universitas Asa Indonesia, 2015)
Purpose- of this study is to findout the effet of compensation on work motivation at Starbuck Jakarta Design/methology/approach- There are 90 respondents with questionnaire. The method that are being used is descriptive method, historical method and documentation method. statistic method is for analyzing incoming data is a simple regression. Findings- Compensation has a direc t effect on Barista’s work motivation that need to be paid attention by management. Research limitations-Limitation on occupation as all of respondents are baristas. Practical implications- It is good for management to pay more attention to other reward aiming to extend employees’ retention